THE CHARACTER EDUCATION BUILDING IN BALINESE FIGURATIVE SPEECH WITHIN ECO-CULTURAL SUSTAINABILITY - I Ketut Wardana; Putu Sri Astuti; Niluh Sukanadi (International Journal of Social Science, 2022)
Balinese literature reflects numerous philosophical and spiritual concepts to live in harmony within the social and natural environment. Instead of identifying and describing the types of figurative speech, this study determined whether the figure of speech in Balinese literature reflected the education formation within Eco-cultural sustainability. Through a qualitative approach Balinese simile, metaphor, analogy, and personification found in 51 stanzas written in 7 lines to 10 lines were collected by a note-taking technique to know the dominant use of the figure of speech, characteristics, and education values. Each expression was analyzed using content analysis. The findings revealed that Balinese literature under investigation was composed of 42% comparative figures, 36% contradictive figures, and 22% correlative figures. Simile and metaphor were mostly expressed in Sampik Ingtai and the contradictive figure including hyperbole and irony took the second place. However, the number of animals, nature, and plants used as comparative words-object are rare and nearly extinct. This study enhanced a model of Ecocultural pedagogy to actualize character education for students’ social care and respect for the environment. So, the figure of speech in Balinese literature plays a prominent role in developing students’ affective competence holistically to gain sustainable intelligence, skills, and human value.